Forecasting US housing starts under asymmetric loss - Christian Pierdzioch; Jan-Christoph Ruelke; Georg Stadtmann (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2012)
Survey data of forecasts of the housing market may provide a particularly rich data nvironment for researchers and policymakers to study developments in housing markets. Based on the approach advanced by Elliott et al. (Rev. Ec. Studies. 72, 1197-1125, 2005), we studied the properties of a large set of survey data of housing starts in the United States. We document the heterogeneity of forecasts, analyze the shape of forecasters' loss function, study the rationality of forecasts, and the temporal variation in forecasts.
Keywords: D84; 330; Housing starts; Loss function; Rationality of forecasts